Reconstruction Of The Quintessence Dark Energy Potential From A Gaussian Process - Elizalde, E.; Khurshudyan, M.; Myrzakulov, K.; Bekov, S.
This paper presents the reconstruction of the quintessence dark energy potential in a modelindependent way. Reconstruction relies on a Gaussian process and on available expansion rate data. Specifically, 40-point values of H(z) are used, consisting of a 30-point sample deduced from a differential age method and an additional 10-point sample obtained from the radial BAO method. Results are obtained for two kernel functions and for three different values of H0. This sheds light on the H0 tension problem indicating that it is not just a numerical problem. The model-independent reconstruction of the potential can serve as a reference to constraint available models and construct new ones. В работе представлена реконструкция потенциала квинтэссенции темной энергии способом, независящим от модели. Реконструкция основана на гауссовом процессе и имеющихся данных о скорости расширения. Конкретно, используются 40 точек значений Hz, включающих в себя 30-точечную выборку, полученную с использованием метода дифференциального возраста, и дополнительную 10-точечную выборку, полученную с помощью метода радиального BAO.
Keywords: Astrophysics